1979
DOI: 10.1111/j.1365-2621.1979.tb09110.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Inactivation Rates of Botulinum Toxins A, B, E and F in Some Foods and Buffers

Abstract: Inactivation of botulinurn toxins was determined in selected acid and low acid foods and buffer systems. Heating at 74°C and 79°C gave a biphasic curve when the log of the inactivation of the toxins was plotted against the time of heating. At 74"C, the time for inactivation of 10' LD, ,, of type A toxin per gram of an acid food such as tomato soup to no detectable toxin by mouse assay was an hr. or more. At 85°C the inactivation was very rapid and approached exponential decrease with inactivation to no detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…These results are also in accordance with the findings of an earlier study that applied the same methodology of thermal treatment and measuring ALP activity when investigating the effect of pasteurization on herpes virus infectivity in milk (4). Retrospectively, it is not clear whether the classical work cited above (5,36,42) is as well defined as our current work with respect to the heat transfer applied, the proven comparability to an industrial process, and the toxin preparations used (neurotoxin or toxin complexes and purity of the material).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results are also in accordance with the findings of an earlier study that applied the same methodology of thermal treatment and measuring ALP activity when investigating the effect of pasteurization on herpes virus infectivity in milk (4). Retrospectively, it is not clear whether the classical work cited above (5,36,42) is as well defined as our current work with respect to the heat transfer applied, the proven comparability to an industrial process, and the toxin preparations used (neurotoxin or toxin complexes and purity of the material).…”
Section: Discussionsupporting
confidence: 80%
“…Later, Bradshaw et al (in 1979) showed that BoNT/A and BoNT/B were more heat stable in beef and mushroom patties than in a phosphate buffer at the same pH (5). Woodburn et al (in 1979) also observed increased heat stability of BoNT/A when 1% gelatin was added to a phosphate buffer (42). Recently, it has been shown that the molten-globule-like character of BoNT and its interaction with NAPs are responsible for variations in physical stability at different pH values (6,7).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ultrahigh-temperature (UHT) pasteurization (performed to provide extended shelf life) appears capable of completely inactivating botulinum toxin in milk, but UHT milk has not been embraced by U.S. consumers. Nonetheless, it is worthwhile to perform pasteurization studies to determine whether a more potent inactivation process can be used without compromising nutrition or taste, particularly because the inactivation rate appears to be quite sensitive to the pasteurization temperature and time in the neighborhood of the current pasteurization formula (7). Reducing the time between silo cleanings decreases the number of people poisoned in, at most, a linear manner, but more frequent cleanings would not only increase variable material and labor costs but would possibly require fixed investments in additional silos.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, botulinum toxins are inactivated within 5 min at 85° C or corresponding heat treatment of lower temperatures for longer times. 20 This review article focuses on reported temperatures and temperature histories in food preparation and processing as well as selected factors affecting these histories. Most publications report temperature data for only a few selected foods and conditions of preparation.…”
mentioning
confidence: 99%